Design, synthesis, and structure-activity relationship studies of dual Plasmodium falciparum phosphatidylinositol 4-kinase and cGMP-dependent protein kinase inhibitors - Gachuhi, Samuel Njoroge (Department of Chemistry, 2022)
Malaria is a life-threatening disease caused by protists in the genus Plasmodium and transmitted by the female Anopheles mosquito. Amongst five species which infect humans, Plasmodium falciparum (Pf) causes the severest form of the disease. Although significant efforts have been made to reduce the overall impact of malaria in endemic regions, the ever emergence and continuous spread of parasite resistance to available chemotherapeutics, threatens to undermine advances made thus far. In addition, the current portfolio of drugs is non-effective in addressing chemoprotection, transmission blockade and relapse in P. vivax and P. ovale species. Thus, drugs targeting multiple stages of the parasite life cycle and of low risk to resistance, are highly desirable to support malaria elimination and/or eradication efforts. Considering the success of human kinase inhibitors as anti-cancer drugs and the identification of Plasmodium kinases as promising targets for malaria chemotherapy, this study aimed to optimize anti-plasmodium phosphatidylinositol 4-kinase (PI4K) and the cGMP-dependent protein kinase (PKG) inhibitors, based on two distinct chemotypes. Plasmodium PI4K and PKG are validated targets, each with the potential to deliver pan-stage active compounds with potentially moderate to low risk of resistance. Part 1 of this study focused on the repositioning of the oncological clinical Phase-1 mammalian target of rapamycin (mTOR) inhibitor, MLN0128, as a dual Plasmodium PI4K/PKG inhibitor for malaria. MLN0128 was identified by GlaxoSmithKline (GSK) Cellzome facility as a Plasmodium multi-kinase inhibitor with potent PI4K and PKG inhibitory activity. In this study, an in silico-guided structural modification strategy was undertaken towards optimizing dual Plasmodium kinase inhibition and anti-plasmodium activity while also mitigating potency against its oncological human target, mTOR and off-target PI4KIIIb (Figure 1). Arising from this work, analogues equipotent against both the chloroquine sensitive (PfNF54) and multi-drug resistant (PfK1) strains simultaneously targeting PI4K and PKG were identified. Docking studies using a PfPI4K homology model and a PvPKG crystal structure discerned the molecular features responsible for the high affinity of the inhibitors for these Plasmodium targets. Benzyl analogues containing a fluoro or chloro group at the meta or para positions displayed high anti-plasmodium activity with potent PvPI4K inhibition but weak PfPKG inhibition. Notable analogues included 7 (PfNF54 IC50 = 0.029 µM; PvPI4K IC50 = 0.007 µM; PfPKG IC50 > 2 µM) and 35 (PfNF54 IC50 = 0.086 µM; PvPI4K IC50 = 0.008 µM; PfPKG IC50 > 10 µM). Introduction of basic or pyridyl substituents proved important for dual Plasmodium kinase activity as exemplified by the active anti-plasmodium pyridyl analogues 44 (PfNF54 IC50 = 0.104 µM; PvPI4K IC50 = 0.004 µM; PfPKG IC50 = 0.834 µM) and 49 (PfNF54 IC50 = 0.189 µM; PvPI4K IC50 = 0.006 µM; PfPKG IC50 = 0.384 µM). In addition, the two compounds displayed low cytotoxicity against the Chinese Hamster Ovarian cell line, with a favorable selectivity index (CHO; SI > 100), low human ether-a-go-go-related gene (hERG) activity (IC50 > 10 µM) and high metabolic stability against human, rat, and mouse (H/R/M) liver microsomes (> 75% remaining after 30-min incubation). Selected compounds from the series also showed the potential for transmission blockade with specificity for stage IV/V gametocytes (IC50 < 1 µM). Furthermore, human off-target PI4KIIIb profiling displayed low activity (< 5% inhibition at 1 µM) for two representative compounds. However, the most promising compounds demonstrated sub-optimal solubility (< 50 µM) and high human mTOR inhibitory activity, issues that necessitate further optimization for progression of this scaffold as an antimalarial chemotype. Part 2 of the study focused on the improvement of solubility, mitigating the hERG liability, and retaining dual Plasmodium PI4K/PKG activity of an established anti-malarial imidazopyridine scaffold. Medicinal chemistry optimization strategies largely revolved around the incorporation of water solubilizing features (Figure 2). Thus, a series of phenyl carboxamides were appended on the left-hand side of the core scaffold while phenyl sulfinyl and sulfonyl moieties were explored on the right-hand side. Incorporation of these features led to several active analogues (PfNF54 IC50 < 1 µM) with high aqueous solubility (> 100 µM). Compounds displayed potent PvPI4K inhibition but weak PfPKG inhibition (IC50 > 1 µM) in enzyme assays. Four compounds, including one sulfoxide analogue, displayed high stability when incubated with H/R/M liver microsomes in microsomal metabolic stability assays. These features also mitigated hERG activity as five analogues tested displayed an IC50 > 10 µM. Ultimately, a front-runner lead compound (86; GS1 16) with high biological activity and a good safety profile (PfNF54/PfK1 = 0.063/0.100 µM; PvPI4K IC50 = 0.003 µM; CHO SI > 793), optimal solubility (195 µM), favorable microsomal metabolic stability (H/R/M = 96/85/88%) and low affinity on the hERG-encoded potassium channel (IC50 = 44.80 µM), was identified for further progression.